2008
DOI: 10.2337/db08-0184
|View full text |Cite
|
Sign up to set email alerts
|

The Human Lipodystrophy Gene BSCL2/Seipin May Be Essential for Normal Adipocyte Differentiation

Abstract: OBJECTIVE-Berardinelli-Seip congenital lipodystrophy type 2 (BSCL2) is a recessive disorder featuring near complete absence of adipose tissue. Remarkably, although the causative gene, BSCL2, has been known for several years, its molecular function and its role in adipose tissue development have not been elucidated. Therefore, we examined whether BSCL2 is involved in the regulation of adipocyte differentiation and the mechanism whereby pathogenic mutations in BSCL2 cause lipodystrophy.RESEARCH DESIGN AND METHOD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
172
5
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 189 publications
(189 citation statements)
references
References 23 publications
10
172
5
1
Order By: Relevance
“…Genetic mutation of LD-related proteins such as, seipin (Magre et al 2001), caveolin-1 (Kim et al 2008), PTRF/cavin1 (Hayashi et al 2009;Rajab et al 2010), and 1-acylglycerol-3-phosphate-O-acyltransferase 2 (Agarwal et al 2002), which is a critical enzyme in TG and phospholipid synthesis, has been shown to cause lipodystrophies. The mechanism that seipin mutation leads to lipodystrophy may not be directly related to its effect on LD formation because it also affects a transcriptional cascade that drives adipogenesis (Payne et al 2008;Chen et al 2009). …”
Section: Lipid Droplets and Disease Diseases Related To Lipid Storagementioning
confidence: 99%
“…Genetic mutation of LD-related proteins such as, seipin (Magre et al 2001), caveolin-1 (Kim et al 2008), PTRF/cavin1 (Hayashi et al 2009;Rajab et al 2010), and 1-acylglycerol-3-phosphate-O-acyltransferase 2 (Agarwal et al 2002), which is a critical enzyme in TG and phospholipid synthesis, has been shown to cause lipodystrophies. The mechanism that seipin mutation leads to lipodystrophy may not be directly related to its effect on LD formation because it also affects a transcriptional cascade that drives adipogenesis (Payne et al 2008;Chen et al 2009). …”
Section: Lipid Droplets and Disease Diseases Related To Lipid Storagementioning
confidence: 99%
“…BSCL2 is a protein of unknown function that localises to the endoplasmic reticulum (ER; Agarwal & Garg 2004, Szymanski et al 2007. Although initially reported to be most highly expressed in the brain, it is also highly expressed in adipocytes (Magre et al 2001, Payne et al 2008. Several studies have suggested that BSCL2 may be involved in lipid droplet formation and is localised at points of contact between nascent lipid droplets and the ER membrane; however, its precise involvement in this process remains to be elucidated (Szymanski et al 2007, Fei et al 2008, Boutet et al 2009).…”
Section: Induction Of Adipogenic Gene Expressionmentioning
confidence: 99%
“…The failure of TAG synthesis therefore provides a very plausible explanation for lipodystrophy in patients with genetic defects in the AGPAT2 gene. However, cellular studies have also demonstrated that disruption of AGPAT2 or BSCL2 inhibits not only lipid synthesis but also the normal induction of adipogenic gene expression during fat cell development (Gale et al 2006, Payne et al 2008. This may reflect the tight co-regulation of gene expression and lipid droplet formation in developing adipocytes or indicate that these proteins possess functions in addition to their proposed roles in lipogenesis.…”
Section: Tag Synthesismentioning
confidence: 99%
“…They described nonsense, frameshift, deletion, insertion, and missense mutations associated with CGL in BSCL2 and called the protein "seipin" (Magre et al 2001). Seipin is an integral ER membrane protein and mainly expressed in adipose tissue, brain, and testis (Payne et al 2008;Magre et al 2001). Lundin et al determined the membrane topology of seipin showing that this protein spans the ER membrane twice with the C-and N-termini facing the cytoplasm and a glycosylation site in the luminal segment (Lundin et al 2006).…”
Section: Introductionmentioning
confidence: 99%